Transcriptomic analysis reveals differential activation of microglial genes after ischemic stroke in mice. (21st April 2017) - Khan, Akbar; Ju, Furong; Xie, Wenguang; Tariq Hafeez, Muhammad; Cheng, Xiaofeng; Yang, Zhijie; Zhu, Lirui; Li, Ting; Zhang, Shengxiang
Highlights: Digital gene expression of ischemic tissue after photothrombosis. Larger microglial genes were altered at 2 days as compared to 7 days after stroke in response to ischemia. Over 74% genes were identified as microglial genes after ischemia. Pathways analysis revealed novel information of up- and down-regulated genes in progression of ischemia. Abstract: Microglia are immune cells in the brain and play a pivotal role in the progression of ischemic injury, but the gene expression and signaling pathways related to the activation of microglia following ischemia remain unclear. In our experiment, we used digital gene expression (DGE) analysis to profile the transcriptome of ischemic tissue in a photothrombosis model. DGE analysis identified that a total of 749 genes were differentially regulated (643 up-regulated and 106 down-regulated) after 2 days and 7 days following stroke. We found 74.5% of these differentially expressed genes were microglial genes. Gene ontology (GO) analysis categorizes these differentially expressed genes at 2 days and 7 days to specific biological processes such as inflammatory response, cell activation, cell proliferation, and chemokine and cytokine production. Our data demonstrated that a large number of microglial genes were highly regulated at 2 days after stroke, but the number of differentially expressed genes had reduced drastically by 7 days. Importantly, some of the differentially expressed microglial genes at 7 days did not show differential expression at 2 days after stroke. DGE analysis indicated that specific genes related to microgliosis were regulated after ischemia. Consistent with the changes in transcriptome, the results from histological analysis of transgenic mice revealed that the microglia proliferated and aggregated surrounding the ischemic core during the period from 2 days to 7 days following photothrombosis. Together, these results suggested that transcriptomic changes in microglial genes after stroke may have a profound implication for pathophysiology and treatment of stroke.